Socialization of the Occupational Safety and Health Management System at PT. Target Kelola Securindo - Muhamad Aziz; Salsabila, Herlina Thania; Taufiqi, Ilham Fajar; Ramadhan, Rifki; Dewanti, Rizky Fara Kartika; Handayani, Yusnita; Nasution, M. Islam (Jurnal Pengabdian Masyarakat Bestari, 2024)
Students from the D-IV K3 Study Program at the Employment Polytechnic carried out Community Service activities aimed at increasing understanding regarding the implementation of the Occupational Safety and Health Management System (SMK3) based on Government Regulation Number 50 of 2012. This activity was carried out for 40 employees of PT Target Kelola Securindo. The implementation method used is in the form of hybrid Project Based Learning via face-to-face and online via Zoom with lecture and question and answer methods. Based on the pretest and posttest that have been carried out, the results of this Community Service activity are in the form of an increased understanding of PT Target Kelola Securindo employees regarding the implementation of the Occupational Safety and Health Management System (SMK3) based on Government Regulation Number 50 of 2012.